2017
DOI: 10.1002/ajh.24714
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting survival in chronic lymphocytic leukemia patients developing Richter syndrome transformation into Hodgkin lymphoma

Abstract: We hereby report the clinical and biologic features of 33 of 4680 (0.7%) patients with chronic lymphocytic leukemia (CLL), managed at 10 Italian centers, who developed Hodgkin lymphoma (HL), a rare variant of Richter syndrome. The median age at CLL and at HL diagnosis were 61 years (range 41-80) and 70 years (range 46-82), respectively, with a median interval from CLL to the diagnosis of HL of 90 months (range 0-258). In 3 cases, CLL and HL were diagnosed simultaneously. Hl was characterized by advanced stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 38 publications
5
46
6
Order By: Relevance
“…Whether this is a true phenomenon is unclear since it might result from the fact that in real life histopathology, verification of disease progression (lymphadenopathy with concomitant B symptoms) is rather made in patients with low than increasing lymphocyte counts. Our results are similar to the results of Mauro et al and Parikh et al (median absolute lymphocyte count of 1.7 × 10 9 ) but contrast the results of Tadmor et al, where a significant proportion of patients still had lymphocytosis at HvRS diagnosis . The biological and clinical significance of lymphopenia in advanced CLL/SLL is unknown although lymphopenia is a well‐known adverse prognostic factor in classical HL .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Whether this is a true phenomenon is unclear since it might result from the fact that in real life histopathology, verification of disease progression (lymphadenopathy with concomitant B symptoms) is rather made in patients with low than increasing lymphocyte counts. Our results are similar to the results of Mauro et al and Parikh et al (median absolute lymphocyte count of 1.7 × 10 9 ) but contrast the results of Tadmor et al, where a significant proportion of patients still had lymphocytosis at HvRS diagnosis . The biological and clinical significance of lymphopenia in advanced CLL/SLL is unknown although lymphopenia is a well‐known adverse prognostic factor in classical HL .…”
Section: Discussionsupporting
confidence: 88%
“…All analyzed patients were diagnosed with advanced stage Hodgkin lymphoma and the majority of them presented with B symptoms, and 50% had an IPS greater than or equal to 4—similar with other studies . The most prevalent subtype was nodular sclerosis (NS), unlike in other studies where mixed cellularity (MC) predominated .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…CLL patients can develop so‐called Richter syndrome (RS), which is when the disease transforms into a high‐grade lymphoma (Rossi and Gaidano, ), most commonly to DLBCL (2–7% of CLL patients in clinical trials) and HL (0.4–0.7% of CLL patients) (Mauro et al ., ). An analysis of IGHV‐D‐J genes revealed that 80% of the DLBCL‐RS are clonally related to the preceding CLL phase, while this is true for only 40–50% of HL‐RS.…”
Section: Chronic Lymphocytic Leukaemia and Related Lymphomasmentioning
confidence: 97%